Modeling multimodal travel corridor using differential complementarity system approach - Du, Bo (2015)
Differential complementarity system approach is applied to model the travel corridor equilibrium in both spatial and spatial-temporal scenarios, which could capture multimodal transportation systems (i.e., highway and railway), heterogeneity, congestion effects, flow dynamics along the corridor. The static model is applied in the specific context of park-and-ride services planning. With the aid of this modelling method, this study further seeks to find the optimal time-distance based road toll scheme to achieve best system performance. Besides, to highlight the effect of urban density distribution to the corridor transportation system performance, this study also aims to find out the optimal density distribution profile. With a set of numerical experiments, multimodal equilibrium patterns, optimal toll scheme and urban density distribution are obtained. In the end, with the geometric programming method, both deterministic and stochastic user equilibrium based continuous network design problems are solved with promising results.